Benny and Penny in The toy breaker : a Toon Book - Hayes, Geoffrey (New York : Toon Books, 2010)
Benny and Penny try to hide their toys from cousin Bo so he will not break them, but the trio then struggle to find something fun to do.
Booklist
Horn Book
School Library Journal
Booklist, March 2010
Horn Book, July 2010
Kirkus Review, April 2010
Keywords: Brothers and sisters -- Comic books, strips, etc -- Juvenile fiction; Bullying -- Comic books, strips, etc -- Juvenile fiction; Cousins -- Comic books, strips, etc -- Juvenile fiction; Mice -- Comic books, strips, etc -- Juvenile fiction; Brothers and sisters -- Fiction; Bullies -- Fiction; Cartoons and comics; Cousins -- Fiction; Mice -- Fiction; Bullies -- Comic books, strips, etc -- Fiction; Comic books, strips, etc; Cousins -- Comic books, strips, etc -- Fiction; Graphic novels; Mice -- Comic books, strips, etc -- Fiction; Siblings -- Comic books, strips, etc -- Fiction; Graphic novels